Feasibility of pre-treating wastewater/water to prevent /minimize reverse osmosis(RO) membrane biofouling using combined UV/Ozone processes - Chew, Delvis Boon Ping (2017)
As biofouling is a prevalent problem in Reverse Osmosis membranes, the use of advance oxidation processes (AOP) to solve this issue has been researched on by many. This study focuses on the effect of combine UV/Ozone advance oxidation process in inactivating a model bacteria. Pseudomonas aeruginosa (PA01) was chosen as it is one of the common opportunistic bacteria that has been detected in biofilms in RO membranes. A stable consistent PA01 culture was obtained and exposed to UV/Ozone. Ozone strength was varied between 100-400mg/h while keeping the UV strength constant at 2.5W. Based on the results, the inactivation effiency was able to reach 100% within 1 minute for all experiments carried out. The kinetic graph was plotted and has shown that the rate constant increases with increase ozone strength. Results has concluded that the use of 400mg/h ozone strength combined with 2.5W UV-C lamp has the best result for killing PA01 of various concentrations within 10 seconds. Energy efficiency was calculated and has shown that 400mg/h ozone strength combined with 2.5W UV-C lamp is the most energy efficient when compared with 400mg/h ozone and 2.5W UV-C lamp individually. This is likely attributed to the synergic effect of the UV/Ozone combined oxidation process, making it a very powerful disinfectant for PA01, thus being the most energy efficient choice. The combine UV/Ozone process appears to be a very promising treatment to prevent membrane biofouling, thus it is strongly recommended for potential future research to use as a pre-treatment disinfectant.